2008
DOI: 10.1038/mp.2008.135
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of 32 genome-wide linkage studies of schizophrenia

Abstract: A genome scan meta-analysis (GSMA) was carried out on 32 independent genome-wide linkage scan analyses that included 3255 pedigrees with 7413 genotyped cases affected with schizophrenia (SCZ) or related disorders. The primary GSMA divided the autosomes into 120 bins, rank-ordered the bins within each study according to the most positive linkage result in each bin, summed these ranks (weighted for study size) for each bin across studies and determined the empirical probability of a given summed rank (PSR) by si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
187
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(197 citation statements)
references
References 69 publications
5
187
3
1
Order By: Relevance
“…A substantial body of evidence from family, twin and adoption studies indicated that a genetic component underlies increased risk for schizophrenia, although replications of these results have been elusive (Tsuang et al, 2001;Ng et al, 2009;Purcell et al, 2009;Shi et al, 2009;Stefansson et al, 2009;Sun et al, 2010). These data support the idea that schizophrenia involves many genes interacting with one another and with environmental risk factors (Palha and Goodman, 2006;Ruano et al, 2008;Sun et al, 2010).…”
Section: Introductionsupporting
confidence: 75%
“…A substantial body of evidence from family, twin and adoption studies indicated that a genetic component underlies increased risk for schizophrenia, although replications of these results have been elusive (Tsuang et al, 2001;Ng et al, 2009;Purcell et al, 2009;Shi et al, 2009;Stefansson et al, 2009;Sun et al, 2010). These data support the idea that schizophrenia involves many genes interacting with one another and with environmental risk factors (Palha and Goodman, 2006;Ruano et al, 2008;Sun et al, 2010).…”
Section: Introductionsupporting
confidence: 75%
“…In addition, DISC1 has been reported as a risk factor for some neuropsychiatric phenotypes, such as anxiety, neuroticism, emotional stability, chronic fatigue syndrome, and social anhedonia (Chubb et al, 2008;Thomson et al, 2013). It is important to note that a genome scan meta-analysis, which included 32 independent genome-wide linkage scan analyses, did not provide evidence for linkage between DISC1 and schizophrenia (Ng et al, 2009). Also, a meta-analysis carried out by Mathieson et al (2012) using 10 candidate gene studies and three GWASs did not confirm an association between DISC1 and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, family-based linkage studies have identified several chromosomal regions and candidate genes that are associated with the risk for schizophrenia [38,39]. However, none of the results of the linkage studies has passed a genome-wide significance level so far [40]. Subsequently, a multitude of association studies that were recently extended by genome-wide association studies (GWAS) identified only a few common variants that contribute a very small increase in the susceptibility for schizophrenia [41][42][43].…”
Section: Schizophreniamentioning
confidence: 99%